Usp22 deficiency impairs intestinal epithelial lineage specification in vivo - Kosinsky, Robyn L. (Impact Journals LLC, 2015)

(untitled) (Oncotarget)
Epigenetic regulatory mechanisms play a central role in controlling gene expression during development, cell differentiation and tumorigenesis. Monoubiquitination of histone H2B is one epigenetic modification which is dynamically regulated by the opposing activities of specific ubiquitin ligases and deubiquitinating enzymes (DUBs). The Ubiquitin-specific Protease 22 (USP22) is the ubiquitin hydrolase component of the human SAGA complex which deubiquitinates histone H2B during transcription. Recently, many studies have investigated an oncogenic potential of USP22 overexpression. However, its physiological function in organ maintenance, development and its cellular function remain largely unknown. A previous study reported embryonic lethality in Usp22 knockout mice. Here we describe a mouse model with a global reduction of USP22 levels which expresses the LacZ gene under the control of the endogenous Usp22 promoter. Using this reporter we found Usp22 to be ubiquitously expressed in murine embryos. Notably, adult Usp22(lacZ/lacZ) displayed low residual Usp22 expression levels coupled with a reduced body size and weight. Interestingly, the reduction of Usp22 significantly influenced the frequency of differentiated cells in the small intestine and the brain while H2B and H2Bub1 levels remained constant. Taken together, we provide evidence for a physiological role for USP22 in controlling cell differentiation and lineage specification.